PLAYgrounds: Effect of a PE playground program in primary schools on PA levels during recess in 6 to 12 year old children. Design of a prospective controlled trial - Verhagen Evert ALM; Van Willem Mechelen; Toussaint Huub M; Janssen Mirka (BMC, 2011)
Abstract Background The relative number of children meeting the minimal required dose of daily physical activity remains execrably low. It has been estimated that in 2015 one out of five children will be overweight. Therefore, low levels of physical activity during early childhood may compromise the current and future health and well-being of the population, and promoting physical activity in younger children is a major public health priority. This study is to gain insight into effects of a Physical Education based playground program on the PA levels during recess in primary school children aged 6-12. Methods/design The effectiveness of the intervention program will be evaluated using a prospective controlled trial design in which schools will be matched, with a follow-up of one school year. The research population will consist of 6-12 year old primary school children. The intervention program will be aimed at improving physical activity levels and will consist of a multi-component alteration of the schools' playground. In addition, playground usage will be increased through altered time management of recess times, as well as a modification of the Physical Education content. Discussion The effects of the intervention on physical activity levels during recess (primary outcome measure), overall daily physical activity and changes in physical fitness (secondary outcome measures) will be assessed. Results of this study could possibly lead to changes in the current playground system of primary schools and provide structured health promotion for future public health. Trial registration Netherlands Trial Register (NTR): NTR2386